Pengaruh Penggunaan Agregat Batu Gunung Pada Campuran Modifikasi Aspal Dan Oil Sludge Jenis Lataston Terhadap Karakteristik Marshall - Ben Sejahtera; Alfian Malik; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Oil sludge is the result of the last distilation and deposition of petroleum. Oil sludge containing chemical compounds and heavy metals that are harmful to the environment. The management of oil sludge waste that is justified by regulation is by utilizing it into a construction product. This experiment aims to determine the effect of agregate replacement on a mixture of modified asphalt type Hot Roll Sheet – Wearing Course (HRS – WC) and maximum levels of oil sludge that can be used in mixture. In this study, the agregate constituents used mountain rock agregate with variations of oil sludge 2%, 4%, 6%, 8% of asphalt weight. Replacement of constituent aggregates causes an increase in the value of density, VMA, and mixture stability. Effect is caused by good aggregate. Based on Marshall characteristic, replacement agregate increase stability and void in mineral agregate (VMA) value also decrease optimum asphalt content.Keywords: oil sludge, modified asphalt, HRS – WC, Marshall characteristic